Decades of dietary data demonstrate regional food web structures in the Southern Ocean. Issue 1 (9th December 2020) - McCormack, Stacey A.; Melbourne‐Thomas, Jessica; Trebilco, Rowan; Blanchard, Julia L.; Raymond, Ben; Constable, Andrew
Abstract: Understanding regional‐scale food web structure in the Southern Ocean is critical to informing fisheries management and assessments of climate change impacts on Southern Ocean ecosystems and ecosystem services. Historically, a large component of Southern Ocean ecosystem research has focused on Antarctic krill, which provide a short, highly efficient food chain, linking primary producers to higher trophic levels. Over the last 15 years, the presence of alternative energy pathways has been identified and hypotheses on their relative importance in different regions raised. Using the largest circumpolar dietary database ever compiled, we tested these hypotheses using an empirical circumpolar comparison of food webs across the four major regions/sectors of the Southern Ocean (defined as south of 40°S) within the austral summer period. We used network analyses and generalizations of taxonomic food web structure to confirm that while Antarctic krill are dominant as the mid‐trophic level for the Atlantic and East Pacific food webs (including the Scotia Arc and Western Antarctic Peninsula), mesopelagic fish and other krill species are dominant contributors to predator diets in the Indian and West Pacific regions (East Antarctica and the Ross Sea). We also highlight how tracking data and habitat modeling for mobile top predators in the Southern Ocean show that these species integrate food webs over large regional scales. Our study provides a quantitative assessment, based on field observations, of the degree of regional differentiation in Southern Ocean food webs and the relative importance of alternative energy pathways between regions. Abstract : Understanding and detecting broadscale change in Southern Ocean ecosystems will rely on understanding the processes that differentiate and maintain food web structure and function at a regional level. Using the largest circumpolar dietary database ever compiled, we tested existing hypotheses on the relative importance of mid‐trophic level organisms in providing pathways to transfer energy to higher predators across the four major oceanic sectors of the Southern Ocean. We used network analyses and generalizations of taxonomic food web structure to confirm that while Antarctic krill are dominant in the mid‐trophic level for the Atlantic and East Pacific food webs, mesopelagic fish and other krill species are dominant contributors to predator diets in the Indian and West Pacific regions.